Meiotic analysis in induced tetraploids of Brachiaria decumbens Stapf - Simioni, Carine (2014)
The meiotic behavior of three tetraploid plants (2n=4x=36) originated from somatic chromosome duplication of sexually reproducing diploid plants of Brachiaria decumbens was evaluated. All the analyzed plants presented abnormalities related to polyploidy, such as irregular chromosome segregation, leading to precocious chromosome migration to the poles and micronuclei during both meiotic divisions. However, the abnormalities observed did not compromise the meiotic products which were characterized by regular tetrads and satisfactory pollen fertility varying from 61.36 to 64.86%. Chromosomes paired mostly as bivalents in diakinesis but univalents to tetravalents were also observed. These studies contributed to the choice of compatible fertile sexual genitors to be crossed to natural tetraploid apomicts in the B. decumbens by identifying abnormalities and verifying pollen fertility. Intraespecific crosses should reduce sterility in the hybrids produced in the breeding program of Brachiaria, a problem observed with the interspecific hybrids produced so far.